2018
DOI: 10.1057/s41293-018-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact agenda and the study of British politics

Abstract: This article attempts to discern the nature of impact in relation to the British politics sub-field of political studies. It reviews evidence from REF2014 to establish how political scientists working in this area understood, and tried to demonstrate impact. It critically appraises how the impact agenda is affecting how research into British politics is prioritised, undertaken and disseminated, and question whether this is a good thing for the sub-discipline. The implications of this for the shape of British p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Added to this are the threats of abuse and harassment that women often experience when engaging in public-facing impact work or when cultivating an online research presence – particularly women of colour (Savigny, 2019). We run the risk that impact incentive structures continue in some ways to encourage, in the words of Les Back(2015: 1; see also Hayton, 2018) ‘an arrogant, self-crediting, boastful and narrow’ form of academic work that positions ‘big research stars’ as ‘impact super heroes’, most of whom are senior White men within the Westminster bubble.…”
Section: Mapping Formal and Informal Obstacles To Changementioning
confidence: 99%
“…Added to this are the threats of abuse and harassment that women often experience when engaging in public-facing impact work or when cultivating an online research presence – particularly women of colour (Savigny, 2019). We run the risk that impact incentive structures continue in some ways to encourage, in the words of Les Back(2015: 1; see also Hayton, 2018) ‘an arrogant, self-crediting, boastful and narrow’ form of academic work that positions ‘big research stars’ as ‘impact super heroes’, most of whom are senior White men within the Westminster bubble.…”
Section: Mapping Formal and Informal Obstacles To Changementioning
confidence: 99%
“…As Peter Allen (2019) has pointed out, academic knowledge can, when disseminated into the public domain, afford epistemic status and value to particular media claims, in part because of the sheen of impartiality and objectivity that is assumed to accompany scholarly research. For our part, academics are increasingly being incentivised to cultivate closer links with those -journalists, politicians, policy makers -who might disseminate as well as implement our knowledge (Hayton 2018).…”
Section: On Reflexivity and Politicised Scholarshipmentioning
confidence: 99%
“…The third problem is to do with a certain squeamishness towards the affective and emotional dynamics of politics. This is mostly manifest as an absence, that is, a discussion of politics in terms of public opinion, party policy programmes and so on without consideration of the feelings and affects that underpin them (see Hayton, 2018). As Foster et al (2013: 568) found in a widely cited analysis of politics and international relations (IR) undergraduate degree programmes in the UK, ‘there is considerable bias towards institutionalised forms of power located within and through institutions, government and governance’, which comes at the expense of a consideration of the role of the private sphere and the affective dynamics of political life.…”
Section: Political Science and The Problem Of Social Mediamentioning
confidence: 99%